The Arabidopsis CstF64-Like RSR1/ESP1 Protein Participates in Glucose Signaling and Flowering Time Control - Funck, Dietmar; Clauss, Karen; Frommer, Wolf B.; Hellmann, Hanjo A. (Frontiers in Plant Science, 2012)
Mechanisms for sensing and regulating metabolic processes at the cellular level are critical for the general physiology and development of living organisms. In higher plants, sugar signaling is crucial for adequate regulation of carbon and energy metabolism and affects virtually every aspect of development. Although many genes are regulated by sugar levels, little is known on how sugar levels are measured by plants. Several components of the sugar signaling network have been unraveled and demonstrated to have extensive overlap with hormone signaling networks. Here we describe the reduced sugar response1-1 (rsr1-1) mutant as a new early flowering mutant that displays decreased sensitivity to abscisic acid. Both Hexokinase1 (HXK1)-dependent and glucose phosphorylation-independent signaling is reduced in rsr1-1. Map-based identification of the affected locus demonstrated that rsr1-1 carries a premature stop codon in the gene for a CstF64-like putative RNA processing factor, ESP1, which is involved in mRNA 3’-end formation. The identification of RSR1/ESP1 as a nuclear phosphoprotein may explain the impact of protein phosphorylation cascades on sugar-dependent signal transduction. Additionally, RSR1/ESP1 may be a crucial factor in linking sugar signaling to the control of flowering time.